Extreme lows of wheat production in Brazil. (30th September 2021) - Nóia Júnior, Rogério de Souza; Martre, Pierre; Finger, Robert; van der Velde, Marijn; Ben-Ari, Tamara; Ewert, Frank; Webber, Heidi; Ruane, Alex C; Asseng, Senthold
Abstract: Wheat production in Brazil is insufficient to meet domestic demand and falls drastically in response to adverse climate events. Multiple, agro-climate-specific regression models, quantifying regional production variability, were combined to estimate national production based on past climate, cropping area, trend-corrected yield, and national commodity prices. Projections with five CMIP6 climate change models suggest extremes of low wheat production historically occurring once every 20 years would become up to 90% frequent by the end of this century, depending on representative concentration pathway, magnified by wheat and in some cases by maize price fluctuations. Similar impacts can be expected for other crops and in other countries. This drastic increase in frequency in extreme low crop production with climate change will threaten Brazil's and many other countries progress toward food security and abolishing hunger.